Adenovirus E1A represses cardiac gene transcription and reactivates DNA synthesis in ventricular myocytes, via alternative pocket protein- and p300-binding domains. - Kirshenbaum,LA; Schneider,MD (J Biol Chem, 1995)
To examine the potential impact of disrupting "pocket" protein function on cardiac differentiation and growth, we introduced 12 S E1A genes into neonatal ventricular myocytes, by adenoviral gene transfer. In the absence of E1B, E1A was cytotoxic, with features typical of apoptosis. In the presence of E1B, E1A preferentially inhibited transcription of cardiac-restricted alpha-actin promoters, and reactivated DNA synthesis in cardiac myocytes, without cell death. Mutations that abrogate known activities of the amino terminus of E1A, versus conserved region 2, demonstrate that the "pocket" protein- and p300-binding domains each suffice, in the absence of the other, for transcriptional repression and re-entry into S phase.